CONSUMER PERSONAL DATA LEGAL PROTECTION ON ILLEGAL FINTECH LOANS - tifany puspa ardianti; Rani Apriani (fakultas hukum universitas PGRI Semarang, 2023)
Currently, there are many online loans that make it easy for people to access credit. In addition to providing convenience, online loans can also harm the public by disseminating personal data. The protection of the rights of online loan service users is considered not optimal. This study aims to find out about the misuse of technology, especially in financial technology. The research method used is a normative juridical approach, the research phase is a literature study, data collection techniques through document studies and normative qualitative data analysis. The results of the study show that consumer protection and consumer personal data protection are indispensable. In this regard, it is important to review the legal protection of borrowers' personal data in online loan application services and sanctions for violations of personal data. The state has provided consumer protection as regulated in Law Number 21 of 2011 concerning Consumer Protection and Financial Services Authority Regulation Number 6/POJK.07/2022 concerning Consumer and Community Protection in the Financial Services Sector.